Pendidikan Perilaku Hidup Sehat dan Bersih Perspektif Pendidikan Islam Bagi Anak Usia Dini dalam Kenormalan Baru Covid-19 - Muhammad Taufiqurrahman (Insititut Agama Islam Negeri (IAIN) Curup, 2020)
This article aimed to find out how to educate healthy and clean living behaviors in the perspective of Islamic education for early childhood in facing the new normal of Covid-19 which is still continuing today. The method employed is library research that used the Prohpetic Parenting book entitled “Cara Nabi Mendidik Anak (How the prophet educates His children) as the main reading material. Then, the data was analyzed in a literary way by looking for other books or journals that are relevant to the theme discussed. The results reveal that educating children on clean and healthy living habits in their early childhood can be done with two approaches. First, it can be a habitual approach where parents get children to do activities that support health and hygiene in accordance to the Qur'an and hadith in facing new normal such as maintaining health, hand and mouth hygiene, food intake, and a resting pattern. Second, the method approach is that parents must use the right method to show them how to do this habituation. The uswah al hasanah method can be an option for parents to invite children to have a healthy and clean lifestyle in facing this current situation of Covid-19. Therefore, parents must become role models for children in implementing clean and healthy living behaviors along the lines of Qur'an and hadith